2014
DOI: 10.1002/jps.23991
|View full text |Cite
|
Sign up to set email alerts
|

Pairwise Polymer Blends for Oral Drug Delivery

Abstract: Blends of polymers with complementary properties hold promise for addressing the diverse, demanding polymer performance requirements in amorphous solid dispersions (ASDs), but we lack comprehensive property understanding for blends of important ASD polymers. Herein, we prepare pairwise blends of commercially available polymers polyvinylpyrrolidone (PVP), the cationic acrylate copolymer Eudragit 100 (E100), hydroxypropyl methylcellulose acetate succinate (HPMCAS), carboxymethyl cellulose acetate butyrate (CMCAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…36 For the PVP:HPMCAS films, clear signs of miscibility between the 2 polymers could be observed based on evidence of hydrogen-bonding interactions, in agreement with previous reports. 37 The PVP carbonyl peak at 1682 cm À1 developed a shoulder at 1643 cm À1 , assigned to the C¼O of PVP hydrogen bonded to the carboxylic acid OH group of HPMCAS (Fig. 3).…”
Section: Binary Polymer Blendsmentioning
confidence: 99%
“…36 For the PVP:HPMCAS films, clear signs of miscibility between the 2 polymers could be observed based on evidence of hydrogen-bonding interactions, in agreement with previous reports. 37 The PVP carbonyl peak at 1682 cm À1 developed a shoulder at 1643 cm À1 , assigned to the C¼O of PVP hydrogen bonded to the carboxylic acid OH group of HPMCAS (Fig. 3).…”
Section: Binary Polymer Blendsmentioning
confidence: 99%
“…Since little was known about the miscibility behaviour of the different PAOx, besides our recent report on phase separation of PEtOx-PPrOx blends [ 23 ], formulations containing only PAOx were prepared through spray drying or film casting in order to assess the miscibility of both PAOx combinations in the absence of API. Various authors have already highlighted the importance of understanding the miscibility and phase behaviour of a binary carrier mixture in order to fully and correctly understand that of the ternary dispersions with API [ 31 , 32 , 33 ]. Next to that, addition of the API, a third component, could affect the miscibility behaviour of the two polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Ternary SDs are effective strategies for further enhancing the dissolution of poorly water-soluble drugs [ 68 , 82 , 83 , 84 , 85 ]. Enteric coating polymers have been investigated by this approach [ 86 , 87 ]. Ohyagi et al combined hypromellose and Eudragit ® L 100 (or a methacrylic acid copolymer) and showed that the resulting ternary SDs had improved dissolution compared to those of single-polymer SDs [ 86 ].…”
Section: Insoluble Carriers At Low Ph Levels In Sdsmentioning
confidence: 99%